If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12(4 + d) = 0 (4 * 12 + d * 12) = 0 (48 + 12d) = 0 Solving 48 + 12d = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-48' to each side of the equation. 48 + -48 + 12d = 0 + -48 Combine like terms: 48 + -48 = 0 0 + 12d = 0 + -48 12d = 0 + -48 Combine like terms: 0 + -48 = -48 12d = -48 Divide each side by '12'. d = -4 Simplifying d = -4
| X^2-2x+6y+6=0 | | 3x-4=x+14 | | x=1/2(2x-4) | | 9d=54 | | 3(5+5x)=105 | | 6r^4q^-3/2q^2*7r^4q^-5/14r^2q^-3 | | 7x+1+7x=113 | | 2(4+7x)=120 | | 10+5s= | | 12a+18= | | 4(3+8X)=28 | | 3.9q-5.6-5.7q=2.8-3.3 | | 2w+2x-13y+5w+13x+6y= | | 14.9=8.6+09m | | 5(2+s)= | | 3x+8+3x=32 | | x^2-x-66=0 | | 2n+21=3n+24 | | -6(2x+1)=9(-2x-2) | | 11(x-2)=88 | | 7x+10+7x=150 | | 3/8/5/9 | | 82-3x=37 | | 23-8x=11+4x | | 3x^4+8x^2-3=0 | | 3x+2+x=30 | | X+3=2x+2 | | x-12=9-2x | | 3/87/12 | | 8+16=4x | | X+9=-6+6x | | 50k+70=40k+100 |